Language Used in the Royal Teachings of King Fangum - yang, khonesawan (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This article aims to analyze Language used in the royal teachings of King Fa Ngum using Critical Discourse Analysis theory. The research findings reveal seven linguistic strategies employed: 1) the use of terminology that establishes power relationships, 2) grammatical sentence structures, 3) rhetorical methods and linguistic strategies, 4) descriptions of rituals to establish sacredness, 5) the use of compound words and word pairs, 6) legitimization strategies, and 7) references to social and economic strategies. The language in these royal proclamations functions to establish governing authority, define social regulations, and construct legitimacy through connections with beliefs and historical precedents.